Epigenome-wide Association Study of Plasma Phylloquinone Response to Phylloquinone Supplementation (OR31-04-19). (13th June 2019) - Kelly, Jennifer; Westerman, Kenneth; Ordovas, Jose M; Booth, Sarah
Abstract: Objectives: Genetics explains a small amount of the variability in the response of plasma phylloquinone to phylloquinone intake. Whether epigenetic modifications, which reflect interactions between the genome and environment, are related to the plasma phylloquinone response to supplementation has not been examined. The objective of this study was to conduct an epigenome-wide association study (EWAS) to identify genetic loci whose methylation levels associate with changes in circulating phylloquinone in response to phylloquinone supplementation. Methods: We used data from a 3-year, randomized controlled, phylloquinone supplementation (500 ug/d) trial in healthy older adults. One hundred four white participants in the supplementation group who passed filters for adherence to the protocol (mean age = 68(5.0) years, 56% female) were classified as responders or non-responders according to their change in plasma phylloquinone. Of these, 24 participants with the smallest (non-responders) and 24 participants with the largest (responders) change in plasma phylloquinone were selected for DNA methylation analysis. DNA was isolated from baseline blood samples. Bisulfite-converted DNA for these 48 individuals was analyzed using the Illumina MethylationEPIC microarray platform at the Yale Center for Genome Analysis in New Haven, CT. The association of responder status with methylation beta-value at each site was examined using logistic regression adjusted for control-probe principal components. Results: Forty (38%) of the 104 participants had changes in plasma phylloquinone that classified them as non-responders. A single CpG site (cg10918016 in NCOR2 ) was associated with plasma phylloquinone responder status at genome-wide Bonferroni level of significance ( P  < 6.4 × 10 −8 ). In the presence of moderate genomic inflation (λ = 1.21), 5239 sites showed suggestive associations (Benjamini-Hochberg FDR < 0.2). Conclusions: DNA methylation levels may contribute toward the inter-individual plasma phylloquinone response to supplementation. Larger studies in diverse populations are warranted to clarify the causal influence of methylation on the vitamin K status. Funding Sources: Study supported by the USDA Agricultural Research Service under Cooperative Agreement No. 58-1950-7-707, NHLBI T32HL069772, and the Gerald Cassidy Student Research Award. * JMK and KW contributed equally to this research. Supporting Tables, Images and/or Graphs: